Opportunities and achievements of using massive parallel sequencing in the diagnosis of neurodevelopmental diseases - T. V. Kozhanova (Эпилепсия и пароксизмальные состояния)
The contribution of genetic factors to development of neurological diseases has long been recognized, and the majority of the advances coupled to using molecular genetic technologies resulted in identifying genes associated with the pathology of developing nervous system. The review is aimed at demonstrating opportunities and achievements of using massive parallel sequencing technology in the diagnosis of a disease with damage to nervous system. Currently, next-generation sequencing (NGS) technology in the genetic diagnosis of epilepsy relies on targeted gene panels, whole exome sequencing or whole genome sequencing. Integrating genetic and genomic analysis into clinical practice to establish clear molecular diagnoses for previously undiagnosed patients will avoid further unnecessary diagnosis and therefore lead to greater healthcare cost savings over time. The use of biomarkers will contribute to the prediction of disease outcome and therapy decision-making.